Materialização e (re)interpretação do debate epistemológico em um currículo de formação em Educação Física - Alves, Cláudia Aleixo (2014)
This study aims to investigate how the epistemological debate of Physical Education, composed mainly from the 1980s, is embodied in a formal curriculum of training of teachers, as well as understanding the interpretations and reinterpretations that the curriculum makes of this debate over time. The prescribed curriculum comprises the examined undergraduate pedagogical project, full degree in Physical Education of the Federal University of Minas Gerais. As a methodological procedure, the documentary analysis of the pedagogical project in question and documents that helped its preparation was utilized, as well as interviews with some of the teachers who participated in the organization of the curriculum in an attempt to grasp the context that also involved its preparation. Given the polarities present in the epistemological debate of the area, the elaboration of a curriculum document, which involves the participation of teachers with different interpretations of this debate, ultimately generates tensions and conflicts that, in turn, may materialize in the curriculum. Given the understanding of the curriculum as a document that expresses a field of struggles and power, we are left with the question of a curriculum of training of teachers. This research aims to investigate how the epistemological debate of Physical in Physical Education that expresses a single epistemological identity, since the polarities and divergences of the area, not only epistemological, but also politics make themselves present at the time of preparing this document.